A randomised trial of a remote home support programme for infants with major congenital heart disease. Issue 20 (11th August 2012) - McCrossan, Brian; Morgan, Gareth; Grant, Brian; Sands, Andrew J; Craig, Brian G; Doherty, Nicola N; Agus, Ashley M; Crealey, Graine E; Casey, Frank A
Abstract : Objectives: To assess the sustainability, clinical utility and acceptability to clinicians and parents of a tele-homecare programme for infants with major congenital heart disease (CHD), and to evaluate the impact on healthcare resource use. Design: Randomised control trial. Setting: UK tertiary congenital cardiac centre. Participants: 83 infants with major CHD. Intervention: Participants were randomised to one of three groups: video-conferencing support (n=35), telephone support (n=24) and a control group (n=24). Patients in the two intervention groups received regular, standardised remote consultations. Video-conferences (VCs) were facilitated by Integrated Systems Digital Network lines and replaced by home broadband connections later in the study. Main outcome measures: Healthcare resource use, utilisation including hospitalisation, clinicians' opinions on utility and quality of interventions, parental opinions on quality of interventions. Results: Clinicians were more confident making medical decisions following VCs compared with telephone consultations (p=0.01). Both VC and telephone support were very well received, but parents expressed significantly higher levels of satisfaction with VC support (p=0.001). Healthcare resource use was 37% lower in the video-conferencing group compared with both telephone support and control groups (p<0.001), as was the risk of hospitalisation (p=0.006). Direct health service costs were significantly lower in the video-conferencing group (p<0.05). Conclusions: A tele-medicine home support programme for families of infants with major CHD is feasible, sustainable and effective. Home support with video-conferencing is superior to telephone consultations. Parents are highly satisfied with tele-homecare. Tele-homecare significantly reduces health service utilisation and may reduce health service costs.